The impact of justice on the Roman Empire : proceedings of the thirteenth workshop of the International Network Impact of Empire (Gent, June 21-24, 2017) / edited by Olivier Hekster, Koenraad Verboven. - Hekster, Olivier,; Verboven, Koenraad, (Impact of Empire, 2019)
The Impact of Justice on the Roman Empire discusses ways in which notions, practice and the ideology of justice impacted on the functioning of the Roman Empire. The papers assembled in this volume follow from the thirteenth workshop of the international network Impact of Empire. They focus on what was considered just in various groups of Roman subjects, how these views were legitimated, shifted over time, and how they affected policy making and political, administrative, and judicial practices. Linking all of the papers are three common themes: the emperor and justice, justice in a dispersed empire and differentiation of justice.